Oxysterols regulate encephalitogenic CD4+ T cell trafficking during central nervous system autoimmunity. (January 2015) - Chalmin, F.; Rochemont, V.; Lippens, C.; Clottu, A.; Sailer, A.W.; Merkler, D.; Hugues, S.; Pot, C.
Abstract: Perturbation of steroids pathways is linked to inflammation and chronic diseases, however the underlying mechanism remains unclear. Oxysterols, oxidized forms of cholesterol, are not only essential for bile synthesis and sterol transportation but have recently been shown to contribute to the immune response. In addition, serum oxysterols levels have been proposed as suitable candidate biomarkers for neurological diseases such as multiple sclerosis (MS). However how oxysterols modulate adaptive immunity is unknown and their functions in autoimmunity have not been investigated. The enzyme cholesterol 25 hydroxylase (Ch25h) is the rate limiting step to synthesize the oxysterol 7α, 25-dihydroxycholesterol (7α, 25-OHC) from cholesterol. We here report, using the MS murine model experimental autoimmune encephalomyelitis (EAE), that Ch25h deletion significantly attenuated EAE disease course by limiting trafficking of pathogenic CD4 + T lymphocytes to the central nervous system (CNS). Mechanistically, we show a critical involvement for oxysterols in recruiting leukocytes into inflamed tissues and propose that 7α, 25-OHC preferentially promotes the migration of activated CD44 + CD4 + T cells by binding the G protein-coupled receptor called Epstein-Barr virus induced gene 2 (EBI2). Collectively, our results support a pro-inflammatory role for oxysterols during EAE and identify oxysterols as a potential therapeutic target to treat autoimmune diseases. Highlights: Oxysterols, oxidized forms of cholesterol, promote autoimmunity. Deletion of Cholesterol 25 hydroxylase (Ch25h) attenuates EAE disease. 7α, 25-OHC downstream Ch25h promotes encephalitogenic CD4 + T cells migration. CD4 + cells express Epstein-Barr virus-induced G-protein coupled receptor 2 (EBI2). Monocyte-derived dendritic cells (MoDCs) are a rich source of Ch25h during EAE.